A COMPARISON OF REGULATION OF BITCOIN AS CRYPTO (DIGITAL) CURRENCY - I Gusti Kade Budhi Harryarsana (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2022)
This study is a literature review study aims to compare government policies towards Bitcoin as a digital currency. The government policies studied were the policies of the American, British, Japanese and Indonesian. The data collected were the data of legislation and the results of previous studies. The results of this study found that each country has different policies regarding digital currencies. In America and Singapore, digital currency is considered property and only applies to some circles and areas. Meanwhile, Japan and Indonesia have the similar policy in which prohibiting the use of digital currency as a means of payment. However, this policy is still under review. This study concludes that every country continues to use conventional money as the main means of payment, although it is possible that there will be policy changes in the future. Currently, each country has also conducted special studies on digital currency because there is the possibility of using digital currency for money laundering crimes.